JNK and Autophagy Independently Contributed to Cytotoxicity of Arsenite combined With Tetrandrine via Modulating Cell Cycle Progression in Human Breast Cancer Cells - Bowen Yu; Bowen Yu; Bo Yuan; Bo Yuan; JingZhe Li; Anna Kiyomi; Hidetomo Kikuchi; Hideki Hayashi; Xiaomei Hu; Mari Okazaki; Munetoshi Sugiura; Toshihiko Hirano; et al. (Frontiers Media S.A., 2020)
Novel therapeutic strategies for breast cancer are urgently needed due to the sustained development of drug resistance and tumor recurrence. Trivalent arsenic derivative (arsenite, AsIII) has been reported to induce cytotoxicity in breast cancer cells. We recently demonstrated that AsIII plus tetrandrine (Tetra), a Chinese plant-derived alkaloid, exerted potent antitumor activity against human breast cancer cells, however, the underlying mechanisms for their action have not been well defined. In order to provide fundamental insights for understanding the action of AsIII plus Tetra, the effects of the combined regimen on two breast cancer cell lines T47D and MDA-MB-231 were evaluated. Compared to T47D cells, MDA-MB-231 cells were much more susceptible to the synergistic cytotoxic effects of AsIII and Tetra. Besides the induction of apoptotic/necrotic cell death, S-phase arrest and autophagic cell death were also observed in MDA-MB-231 cells. Exposure of MDA-MB-231 cells to AsIII and Tetra caused the activation of MAPKs. Cytotoxicity of the combined regimen in MDA-MB-231 cell was significantly abrogated by SP600125, a potent c-Jun N-terminal kinase (JNK) inhibitor. However, similar abrogation was not caused by p38 and ERK inhibitors. The addition of either autophagy inhibitors (3-methyladenine or wortmannin) or SP600125 corrected the combined regimen-triggered S-phase arrest, whereas had little effect on the apoptosis/necrosis induction in the cells. Surprisingly, SP600125NC, a negative control for SP600125, significantly strengthened S-phase arrest and the cytotoxicity induced by the combined regimen. The addition of SP600125 did not alter autophagy induction. In conclusion, the cytotoxicity of AsIII combined with Tetra was attributed to the induction of S-phase arrest, apoptotic/necrotic and autophagic cell death. The enhanced cytotoxicity of the two drugs by SP600125NC might be explained by its capability to strengthen S-phase arrest. Our results suggested that JNK and autophagy independently contributed to the cytotoxicity via modulating cell cycle progression. The study further provides fundamental insights for the development of AsIII in combination with Tetra for patients with different types of breast cancer.